Information transparency of firm financing - Antoine L. Noël; Amy Hongfei Sun (Queen's University, Department of Economics, 2021)
We propose an information-based theory of capital structure to address the diversity of firm financing behavior and the variety of optimal financial contracts. Our model features nested information problems of adverse selection and agency cost. We prove that there exists a unique perfect Bayesian equilibrium with novel features: First, three types of optimal contracts arise endogenously, i.e., equity, transparent debt, and opaque debt. Equity and transparent debt are both informationally transparent because these contracts require firms to take on a costly technology for verifying types. Opaque debt, however, merely reflects the general information of firms seeking external funds. Any signaling contract that does not involve costly verification does not survive the equilibrium. Second, the unique equilibrium is either pooling on opaque debt, or mixing with transparent and opaque financing. Third, partial capital structure irrelevance exists in a mixing equilibrium. Fourth, debt weakly dominates equity for all firms that seek external financing. Finally, the optimal debt-to-equity ratio is unique for all firms in a pooling equilibrium, but only for a strict subset of firms in a mixing equilibrium.
Keywords: D82; D86; G32; 330; Optimal Contracts; Capital Structure; External Financing; Asymmetric Information; Information Transparency